Analisis Rekomendasi Peluang Usaha Jajanan Makanan Dengan Teknik VIKOR - Asri Yustika; Sundari Retno Andani; Dedi Suhendro (LPPM STIKOM Tunas Bangsa, 2020)
The research aims to determine the right food snack business opportunities that are able to attract public interest in Pematangsiantar City. The decision support system applied in this study uses the Vikor method. Sources of research data are obtained by observing or interviewing traders who sell food snacks in Pematangsiantar City. The recommendation of food snack business opportunities was carried out by taking 13 samples and using several criteria, including: (K1) initial capital, (K2) operating costs, (K3) profit, (K4) buyers, and (K5) competitors as benchmarks. From the results of research conducted with the Vikor method, it shows that the alternative that ranks first with the smallest Q value is Assorted Ice Cream with a value of Q = 0 as the recommended alternative.